2022
DOI: 10.4103/ijo.ijo_2795_21
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of a new presbyopia pseudophakic intraocular lens: Safety, efficacy and satisfaction

Abstract: Purpose: To evaluate the safety, visual performance, and patient satisfaction of a new presbyopic pseudophakic intraocular lens (IOL). Methods: A prospective non-randomized case-series study was performed in Buenos Aires, Argentina. Patients included in the study underwent a programmed Femtosecond laser assisted cataract surgery (FLACS), performed between October and December 2020, with a 6-month follow-up period. The Intensity (Hanita Lenses) IOL was bilaterally implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…Bianchi implanted the Intensity IOL in 112 eyes of 56 patients. None of them experienced visual loss and 94% had a final refraction within ± 0.5 D; uncorrected and corrected visual acuity in this group did not differ much from our results [ 10 ]. The group of Ehud Assia et al implanted the Intensity SL in 20 patients (40 eyes) and reported a mean uncorrected visual acuity for distance, intermediate and near of 0.03, 0.09 and -0.22 logMAR, respectively; the excellent result for near seems to reflect our experience.…”
Section: Discussioncontrasting
confidence: 51%
“…Bianchi implanted the Intensity IOL in 112 eyes of 56 patients. None of them experienced visual loss and 94% had a final refraction within ± 0.5 D; uncorrected and corrected visual acuity in this group did not differ much from our results [ 10 ]. The group of Ehud Assia et al implanted the Intensity SL in 20 patients (40 eyes) and reported a mean uncorrected visual acuity for distance, intermediate and near of 0.03, 0.09 and -0.22 logMAR, respectively; the excellent result for near seems to reflect our experience.…”
Section: Discussioncontrasting
confidence: 51%